The statistical method in economics and political science : a treatise on the quantitative and institutional approach to social and industrial problems /: a treatise on the quantitative and institutional approach to social and industrial problems. (2018) - Florence, P. Sargant (Philip Sargant), 1890-1982
No abstract available